Effects of dodecyl amine functionalized graphene oxide on the crystallization behavior of isotactic polypropylene. Issue 6 (17th October 2013) - Wang, Hao; Ren, Peng‐Gang; Chen, Yan‐Hui; Yan, Ding‐Xiang; Li, Zhong‐Ming; Xu, Ling
ABSTRACT Dodecyl amine functionalized graphene oxide (DA‐GO)/isotactic polypropylene (iPP) nanocomposites were prepared via solution mixing method. Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), and X‐ray photoelectron spectroscopy (XPS) verified that the DA was successfully grafted onto the surface of graphene oxide. The crystallization behavior of iPP/DA‐GO nanocomposites was investigated by differential scanning calorimetry (DSC) and polarized optical microscope (POM). The DSC results of both isothermal and non‐isothermal crystallization process indicated that the addition of DA‐GO can decrease the half‐time crystallization (t1/2) and elevate crystallization peak temperature (Tp) of iPP. The results of isothermal crystallization kinetics showed that the overall crystallization rates of iPP/DA‐GO nanocomposites, especially with higher DA‐GO content, were much faster than that of neat iPP. During the non‐isothermal crystallization process, the nucleation ability (Φ) of nanocomposites containing 0.05, and 0.5 wt % DA‐GO were 0.83 and 0.69, respectively. And the crystallization activation energy <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zt8vb4m" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ΔEa</alternatives> of iPP decreased from 348.7 (neat iPP) to 309.2 and 283.1 kJ/m2 by addition of 0.05 and 0.5 wt % DA‐GO, respectively. The decrease of Φ and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zt8vb9c" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ln⁡t</alternatives> indicated DA‐GO has strong heterogeneous nucleation effect and can promote the crystallization of iPP significantly. Additionally, POM micrographs showed the DA‐GO in iPP matrix can form more nucleation sites for the spherulite growth. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2014, 131, 40000.